STYLISTIC FUNCTIONS OF IDIOLECT IN “A FAREWELL TO ARMS” BY ERNEST HEMINGWAY (KONFERENSIYA, 2025)
This article explains the stylistic functions of idiolect in Ernest Hemingway’s novel A Farewell to Arms. The study shows how the individual speech of the characters helps to describe their personality, emotions, and relationships. It also gives simple information about Hemingway’s writing style, such as short sentences, easy words, and realistic dialogues. Several examples from the novel are used to show how idiolect makes the story more natural and expressive. The results show that idiolect plays an important role in creating the author’s unique style.